Sunday, October 20, 2013

Given `A= ((4, 3, 2),(5,6,3),(3,5,2));B = ((a, b, c),(d,e,f),(g,h,i))`Find B so that AB = I = BA as follows: First equate entries on the two...

You need to multiply the matrices A and B such
that:


`((4,3,2),(5,6,3),(3,5,2))*((a,b,c),(d,e,f),(g,h,i))
= ((1,0,0),(0,1,0),(0,0,1))`


`((4a+3d+2g, 4b+3e+2h,
4c+3f+2i),(5a+6d+3g, 5b+6e+3h, 5c+6f+3i),(3a+5d+2g, 3b+5+2h, 3c+5f+2i)) =
((1,0,0),(0,1,0),(0,0,1))`


Equating corresponding terms
yields:


`4a+3d+2g = 1
`


`4b+3e+2h = 0`


`4c+3f+2i = 0
`


`5a+6d+3g = 0 `


`5b+6e+3h =
1 `


`5c+6f+3i = 0 `


`3a+5d+2g
= 0 `


`3b+5e+2h = 0
`


`3c+5f+2i = 1`


You need to
consider the equations that contain a,d,g such
that:


`4a+3d+2g = 1
`


`5a+6d+3g = 0 `


`3a+5d+2g =
0`


You need to subtract the third equation from the first
such that:


`a - 2d = 1`


You
need to multiply the first equation by 3 and the second equation by -2 and then you
should add the new equations such that:


`12a + 9d + 6g =
3`


` -10a - 12d - 6g = 0`


`2a
- 3d = 3`


You need to multiply the equation a - 2d = 1 by
-2 such that:


`-2a + 4d =
-2`


Adding this equation to 2a - 3d = 3
yields:


`2a - 3d - 2a + 4d= 3 -
2`


`d = 1 =gt a - 2 = 1 =gt a =
3`


`15+6+3g = 0 =gt 3g = -21 =gt g =
-7`


You need to consider the equations that contain b,e,h
such that:


`4b+3e+2h = 0
`


`5b+6e+3h = 1 `


`3b+5e+2h =
0`


Subtracting the third equation from the first
yields:


`b - 2e = 0 =gt b =
2e`


Substituting 2e for b in the first and second equations
yields:


`11e + 2h = 0 `


`16e +
3h = 1`


You need to multiply by 3 the equation 11e + 2h = 0
and by -2 the equation 16e + 3h = 1 such that:


`33e + 6h =
0 `


`-32e - 6h = -2`


`33e + 6h
-32e - 6h = 0-2`


`e = -2 =gt b =
-4`


`-16-6+2h = 0 =gt 2h = 22 =gt h =
11`


You need to consider the equations that contain c,f,i
such that:


`4c+3f+2i = 0
`


`5c+6f+3i = 0 `


`3c+5f+2i =
1`


`4c+3f+2i - 3c-5f-2i =
-1`


` c - 2f = -1 =gt c = 2f -
1`


Substituting 2f - 1 for c in the first and second
equations yields:


`4(2f-1)+3f+2i = 0=gt 11f + 2i = 4
`


`5(2f-1)+6f+3i = 0 =gt 16f + 3i =
5`


`3(11f+2i) - 2(16f+3i) = 12 -
10`


`33f + 6i - 32f - 6i =
2`


`f = 2 =gt c = 4 - 1 =
3`


`12+6+2i = 0 =gt 2i = -18 =gt i =
-9`


Hence, evaluating the matrix B under
given conditions yields `B = ((3,-4,3),(1,-2,2),(-7,11,-9)).`

No comments:

Post a Comment

Calculate tan(x-y), if sin x=1/2 and sin y=1/3. 0

We'll write the formula of the tangent of difference of 2 angles. tan (x-y) = (tan x - tan y)/(1 + tan x*tan y) ...